Animal Welfare and Livestock Supply Chain Sustainability Under the COVID-19 Outbreak: An Overview - Hashem, Nesrein M.; González-Bulnes, Antonio; Rodriguez-Morales, Alfonso J. (Frontiers in Veterinary Science, 2020)
The COVID-19 pandemic, caused by the emergence of a new strain of coronavirus (SARS-CoV-2) around the end of December 2019, has caused a worldwide public health emergency and a socioeconomic crisis during 2020. The lockdown imposed to cope with the health issues caused by the outbreak of the disease has dramatically challenged and negatively affected all the economic sectors of the modern global economy. Specifically, the livestock sector and its related industries are among the most impacted sectors. This is mainly ascribed to the limitations of animal movement and the decrease of production inputs' availability. Other factors negatively affecting the sustainability of the livestock sector have been the shortage of workers due to the lockdown/curfew, the strong decrease in the purchasing power of the consumer, and the intensification of health care tasks. Such an impact is not only highly relevant because of their economic consequences, but also because of the effects of the lockdown and sanitary rules on animal care and welfare. The current review aims to offer: (a) a comprehensive overview of the impact of COVID-19 on the welfare of farm animals and on the performance of livestock farming systems, on food chain sustainability, and finally, on the global economy and food security; and (b) a prospective outline of alleviation actions.